2023
DOI: 10.1108/yc-03-2023-1707
|View full text |Cite
|
Sign up to set email alerts
|

Beyond labels: segmenting the Gen Z market for more effective marketing

Joeri Van den Bergh,
Patrick De Pelsmacker,
Ben Worsley

Abstract: Purpose The purpose of this study is to identify segments in the Gen Z population (born between 1996 and 2010) in Europe, the USA and Australia, based on brand- and lifestyle-related variables and perceptions about their online activities. This study explores how these segments differ and provide insights into cross-country similarities and differences. Design/methodology/approach An online survey was conducted with 4,304 participants, and cluster analysis and analysis of variance were used to identify and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
(123 reference statements)
0
3
0
Order By: Relevance
“…The positive emotions from pleasure create strong in-centives for consumers to make quick, unplanned purchases for immediate gratification and emotional rewards. Generation Z exhibits a high propensity for engaging with technological advancements (Van den Bergh et al, 2023). This phenomenon can be felt when shopping via the Live TikTok Shop platform.…”
Section: Discussionmentioning
confidence: 99%
“…The positive emotions from pleasure create strong in-centives for consumers to make quick, unplanned purchases for immediate gratification and emotional rewards. Generation Z exhibits a high propensity for engaging with technological advancements (Van den Bergh et al, 2023). This phenomenon can be felt when shopping via the Live TikTok Shop platform.…”
Section: Discussionmentioning
confidence: 99%
“…The fashion industry may have a market expansion opportunity with the 41 percent share of Generation Z. In addition, numerous studies have demonstrated that Generation Z actively purchases and consumes goods from a variety of online marketplaces; thus, it is considered one of the most influential consumer groups (Nghia, Olsen and Trang, 2020;Azhar et al, 2023;Van den Bergh, De Pelsmacker and Worsley, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Several scholarly investigations have been undertaken to examine the purchasing patterns of Generation Z through the lens of generational cohort theory, which emphasizes the characteristics of cohorts (Ismail et al, 2020;Agrawal, 2022;Thangavel, Pathak and Chandra, 2022;Van den Bergh, De Pelsmacker and Worsley, 2023). Another approach used is the Theory of Planned Behavior (Djafarova and Foots, 2022;Pradeep and Pradeep, 2023;Suzianti, Amaradhanny and Fathia, 2023); the theory of Acceptance Model (Lestari, 2019), which uses the gratification theory (Siregar et al, 2023), and social commerce adoption model that focuses on specific platforms (Azhar et al, 2023).…”
Section: Introductionmentioning
confidence: 99%